Bruikbaarheid van alternatieve energiesystemen ter vervanging van hout en kolen in Afrika - Baert, Daniel; Bangurambona, Bonaventure; Kuyken, Hugo (Afrika Focus, 1987)
In the article, the possibility of the use of alternative energy sources (a.e.) in Africa is discussed. The authors give some criteria which have to be fulfilled before a.e. sources can succesfully be applicated. KEYWORDS: alternative energy sources, cooking, heating, photovoltaic generators, refrigeration.